2019
DOI: 10.1088/1748-9326/ab4f96
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model approach for estimating health burden from NO2 in megacities in China: a case study in Guangzhou

Abstract: Background: Nitrogen dioxide (NO 2 ) poses substantial public health risks in large cities globally. Concentrations of NO 2 shows high spatial variation, yet intra-urban measurements of NO 2 in Chinese cities are sparse. The size of Chinese cities and shortage of some datasets is challenging for high spatial resolution modelling. The aim here was to combine advantages of dispersion and land-use regression (LUR) modelling to simulate population exposure to NO 2 at high spatial resolution for health burden calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In addition, several studies have shown that increased exposure to NO 2 can itself result in negative health outcomes, independent of local concentrations of other pollutants (23)(24)(25). The relationships between exposure to pollution and mortality identified by these studies are routinely used to estimate the negative health impacts of human activity (26)(27)(28)(29). For example, long-term exposure to ozone and PM 2.5 resulting from human activity is estimated to cause ~3.8 million premature mortalities each year (30).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that increased exposure to NO 2 can itself result in negative health outcomes, independent of local concentrations of other pollutants (23)(24)(25). The relationships between exposure to pollution and mortality identified by these studies are routinely used to estimate the negative health impacts of human activity (26)(27)(28)(29). For example, long-term exposure to ozone and PM 2.5 resulting from human activity is estimated to cause ~3.8 million premature mortalities each year (30).…”
Section: Introductionmentioning
confidence: 99%
“…We used ADMS-Urban (version 4.2), a state-of-the-art urban scale high resolution quasi-Gaussian dispersion model (McHugh et al, 1997;Owen et al, 2000) to simulate pollutant concentrations. The model has been applied in air quality simulations in cities worldwide including Beijing (Biggart et al, 2020;He et al, 2019;Hood et al, 2018). Dispersion calculations are based on the state of the atmospheric boundary layer which is parameterised based on Monin-Obukhov similarity theory (Venkatram, 1996).…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%
“…We used ADMS-Urban (version 4.2), a state-of-theart urban-scale high-resolution quasi-Gaussian dispersion model (McHugh et al, 1997;Owen et al, 2000). The model has been applied in air quality simulations in cities worldwide including Beijing (Biggart et al, 2020;He et al, 2019;Hood et al, 2018). Dispersion calculations are based on the state of the atmospheric boundary layer, which is parameterised based on Monin-Obukhov similarity theory (Venkatram, 1996).…”
Section: Model Description and Simulation Setupmentioning
confidence: 99%